2016
DOI: 10.1017/iop.2016.89
|View full text |Cite
|
Sign up to set email alerts
|

Why the Qualms With Qualitative? Utilizing Qualitative Methods in 360° Feedback

Abstract: Although the authors of the focal article provide a comprehensive definition of 360° feedback, one exclusionary criterion results in an overly narrow definition of 360° feedback. Specifically, Point 3 in their definition described the criticality of strictly using quantitative methods in collecting 360° feedback. The authors provided a brief rationale by stating, “Data generated from truly qualitative interviews would not allow comparisons between rater groups on the same set of behaviors” (Bracken, Rose, &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…For example, receiving a below average rating on the dimension of adaptability, although succinct, is not incredibly informative. On the other hand, narrative comments allow one to comprehend the reasoning behind numerical ratings (Brutus, ; Kabins, ), providing rich data regarding a person's behaviors within specific contexts and how others perceive them. In this example, information such as “you failed to adopt usage of a new technology system and instead relied on old methods to get work done” would provide much richer information.…”
Section: Brief Overview Of Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, receiving a below average rating on the dimension of adaptability, although succinct, is not incredibly informative. On the other hand, narrative comments allow one to comprehend the reasoning behind numerical ratings (Brutus, ; Kabins, ), providing rich data regarding a person's behaviors within specific contexts and how others perceive them. In this example, information such as “you failed to adopt usage of a new technology system and instead relied on old methods to get work done” would provide much richer information.…”
Section: Brief Overview Of Performance Evaluationmentioning
confidence: 99%
“…At the same time, narrative comments allow for the provision of additional construct‐relevant information not captured by traditional numerical ratings, thus also increasing the bandwidth of measurement. Given the free‐form nature of narratives, raters can elaborate more upon competencies, upon completion of goals, and how the behavior of the employee impacted others (Kabins, ). This might be particularly salient if traditional performance scales are overly broad, such as if managers only produce a single overall rating.…”
Section: Measurement Using Narrative Commentsmentioning
confidence: 99%
“…Qualitative feedback is more likely to trigger behavior change than quantitative performance ratings (Kabins, 2016), especially when comments include prescriptive suggestions for development (Brutus, 2010). A survey of executives who received feedback consisting of both quantitative ratings and anonymous narrative comments found that these executives attended to narrative comments more than they did to numerical ratings (Ferstl and Bruskiewicz, 2000).…”
Section: The Role Of Feedback In Leadership Developmentmentioning
confidence: 99%
“…Brown, Kulik & Lim, 2016), there is a shortage of empirical research into the content of qualitative developmental feedback more broadly (i.e. what is said and how it is said: Kabins, 2016) and whether this differs for men and women in, or aspiring to, leadership roles. Instead, most research has focused on quantitative ratings of performance and issues such as rater agreement in feedback to leaders (Day, Fleenor, Atwater, Sturm & McKee, 2014;Markham, Markjam, & Smith, 2015).…”
Section: The Role Of Feedback In Leadership Developmentmentioning
confidence: 99%
See 1 more Smart Citation